PEMBIAKAN MIKORIZA ASAL AKAR MERANTI (Shorea montigena) DENGAN MENGGUNAKAN CARA LARUTAN - Nuel Patrik Radjabaycolle Bunga; Johan M. Matinahoru; Miranda H. Hadijah (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Meranti (Shorea montigena Slooten) has roots that serve as a habitat for mycorrhizal fungi. These mycorrhizal fungi can be propagated and transmitted to other plant species. Transmission of mycorrhizal fungi can occur in the roots of host plants, if infection has occurred. So far, the process of breeding endomycorrhizal fungi is mostly done in a non-solution way, so this study aims to find an effective solution medium for breeding endomycorrhizal fungi. The method used is the solution method. The research design used was a single factor experiment in a completely randomized design. The single factor is the type of solution media consisting of 5 levels. The treatment was repeated 3 times and each treatment consisted of 5 corn plant seedlings, so the total number of corn plant seedlings was 75 seedlings that were sown for 1 month in the greenhouse, and then inoculated with mycorrhizal solution after the seedlings were 2 weeks old. The parameters observed in this study were mycorrhizal fungal growth (days), mycorrhizal fungal development (cm2), and the percentage of mycorrhizal fungal infection in corn plant roots (%). Based on the results of the study, the type of solution media treatment had a significant effect on the growth and development of endomycorrhiza from the roots of meranti stands. The effective solution media in this study was in the A4 treatment, namely a mixture of rice washing water waste and brown sugar which produced the best average growth and development of endomycorrhiza. In addition, the effectiveness of endomycorrhizal fungi is able to spur the growth of corn plants used as applied media. Endomycorrhizal fungi propagated using this solution procedure have the potential to be developed as a biofertilizer and can improve soil fertility.